Evaluation of ginger (Zingiber officinale Rosc.) varieties in high altitude and tribal zone of Srikakulam district of Andhra Pradesh - K Umajyothi, R Rajyalakshmi, (Journal of Spices and Aromatic Crops, 2014)
The yield performance and simple association between yield and its components were studied in eight varieties of ginger during kharif 2007 and 2008. The variety Suprabha was taller and recorded more number of leaves, tillers plant-1 and number of finger rhizomes plant-1. It produced significantly more fresh rhizome yield of 21.71 t ha-1 than all the other the varieties tested. Among the varieties Chintapalli local produced more number of mother rhizomes plant-1. Number of tillers plant-1, number of mother and finger rhizomes plant-1 and fresh rhizome yield showed high GCV, PCV, heritability and genetic advance as per cent mean. The simple correlation studies indicated that number of tillers plant-1, number of mother and finger rhizomes plant-1 recorded highly significant association with yield.